Destination Branding Sebagai Identitas Visual Dusun Dalem Widodomartani, Sleman, Yogyakarta - Ipung Kurniawan Yunianto (AKSA: Jurnal Desain Komunikasi Visual, 2018)
Dusun Dalem, Widodomartani, is one of the tourist villages in Sleman district of Propinsi Daerah Istimewa Yogyakarta. Dusun Dalem preserves a tourism potential in the form of a bright blue water source in the middle of the hamlet (dusun) shaded by bamboo forest with beautiful nuances. This potential gives a charm for every visitor that makes Dusun Dalem became the belle of new tourist destination in Sleman district. The result of the research showed that although Dusun Dalem in well known, it does not have a representative visual identity yet to increase its value and visitors' awareness. Therefore, the design of destination branding is expected to increase visitors' familiarity and also to add brand awareness of Dusun Dalem.